A idade da representação: a relação entre a arqueologia e a genealogia em Foucault - Soares, Matheus Henrique Borges (2023)
This research aims to demonstrate the mode of the historical conception of the French philosopher Michel Foucault (1926-1984) from his modus operandi, that is, I do not pay attention only to his analytical assumptions in comparison with other historical conceptions that he criticizes, but part of the archeology carried out by the French philosopher. At first, I work with the rupture between the 16th century epistemes with that of the 17th and 18th centuries, the focus of the research is to analyze what Foucault calls the Age of Representation that links the sign to the role of representing, such linking conditioned the emergence of general grammar, natural history and richness analysis. In a second moment, I approach the Foucaultian genealogy that works in complementarity with archeology, in order to link the emergence of a new regime of penalties that arises in the break with the torture, so this new regime of penalties is responsible for establishing a new code criminal law that articulates the advantage of the crime with the disadvantage of the penalty, thus demonstrating that there is a transversality in what became known as classical representationism in the work of Michel Foucault.